Relation between the Increase of Alpha Fetoprotein Serum Level and the Size of Hepatocellular Carcinoma in Multi Slice Computed Tomography Examination - Ika Putri Maharani1, Nifa Koesmarsono1, Budi Laraswati1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Hepatocellular carcinoma can be diagnosed based on the result of Multi Slice Computed Tomography (MSCT) imaging only without histology result confirmation Objective: The aim of the study is to find out the relation between the increase of alpha fetoprotein serum level and the size of hepatocellular carcinoma in MSCT examination in Dr. Soetomo Teaching Hospital. Methodology: This is a retrospective, observational analytic study which uses secondary data. There were 50 samples with hepatocellular carcinoma. The data were collected from the medical records of MSCT subjects and AFP (Alpha-fetoprotein) serum level result. All recorded and analyzed statistically. Results: Of all the 50 samples, 41 are male (82%) and 9 are female (18%). The ages of the samples ranged from 19 to 76 years old with the majority of 51-60 years old in 15 patients (30%). Most distribution of AFP serum level was >400 ng/ml with 29 patients (58%) and tumor size of >5 cm with 49 patients (98%). The analysis using Spearman correlation test shows the correlation value p = 0.418 (p >0.05). Conclusion: There was no relation is found between the increase of alfa fetoprotein serum level and the size of hepatocellular carcinoma in MSCT examination.